360 virtual reality pediatric mass casualty incident: A cross sectional observational study of triage and out‐of‐hospital intervention accuracy at a national conference. Issue 5 (17th August 2020) - Lowe, Jason; Peng, Cynthia; Winstead‐Derlega, Christopher; Curtis, Henry
Abstract: Objective: With adolescent mass casualty incidents (MCI) on the rise, out‐of‐hospital readiness is critical to optimize disaster response. We sought to test the feasibility and acceptability of a 360 Virtual Reality (360 VR) platform for disaster event decisionmaking. Methods: This was a cross‐sectional observational assessment of a subject's ability to triage and perform out‐of‐hospital interventions using a 360 VR MCI module. A convenience sample of attendees was recruited over 1.5 days from the American College of Emergency Physicians (ACEP) national conference in San Diego, CA. Results: Two hundred and seven (207) subjects were enrolled. Ninety‐six (46%) subjects identified as attendings, 66 (32%) as residents, 13 (6%) as medical students, 4 (2%) as emergency medical technicians and 28 (14%) as other. When comparing mean scores between groups, physicians who were <40 years old had mean scores higher than physicians who were >40 years old (8.7 vs 6.5, P < 0.001). Residents achieved higher scores than attendings (8.6 vs 7.5, P = 0.005). Based on a 5‐point Likert scale, participants felt the 360 VR experience was engaging (median = 5) and enjoyable (median = 5). Most felt that 360 VR was more immersive than mannequin‐based simulation training (median = 5). Conclusion: We conclude that 360 VR is a feasible platform for assessing triage and intervention decisionmaking for adolescent MCIs. It is well received by subjects and may have a role as a training and education tool for disaster readiness. In this era of distanced learning, 360 VR is an attractive option for future immersive educational experiences.